1985
DOI: 10.7863/jum.1985.4.12.641
|View full text |Cite
|
Sign up to set email alerts
|

Splanchnic vein measurements in patients with liver cirrhosis: a case-control study.

Abstract: The portal venous system was evaluated by real-time ultrasonography in 100 consecutive cirrhotic patients and 100 pair-matched controls to assess the sensitivity and specificity of ultrasound findings in detecting or excluding cirrhosis. The best discriminant findings were the expiration diameters of the superior mesenteric and the splenic vein and, chiefly. their sum corrected by body surfitce. In cirrhotics the calibers of the splanchnic veins significantly increase in relation to the extent of esophageal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 4 publications
4
16
0
1
Order By: Relevance
“…This impression was confirmed by a paper that demonstrated that the diameters of the superior mesenteric vein and the splenic vein were statistically different in control subjects and in patients with cirrhosis [30]. The best discriminated findings were the expiration measurements [30].…”
Section: Splanchnic Veinsmentioning
confidence: 69%
“…This impression was confirmed by a paper that demonstrated that the diameters of the superior mesenteric vein and the splenic vein were statistically different in control subjects and in patients with cirrhosis [30]. The best discriminated findings were the expiration measurements [30].…”
Section: Splanchnic Veinsmentioning
confidence: 69%
“…Retrospectively, we might have underestimated the diameter of the SMV in the CT scan and the placed stent (diameter 6 mm) may have been too small. It has been shown that the diameter of the SMV changes significantly under respiration (13,14). For the same reason we nowrecommend oversizing of self-expanding nitinol stents by 50 % for stenting of the SMV and a diameter of at least 10 mm should be used in accordance to the SMV stenting techniques of the other working groups(1-3).…”
Section: Discussionmentioning
confidence: 87%
“…An increased caliber of the portal, splenic and mesenteric veins, particu larly if corrected for the body surface, is a sensitive and specific marker of portal hy pertension [19], Moriyasu et al [9] proposed that also the 'congestion index', i.e. the ratio between the cross-sectional area and the blood velocity in the portal vein, measured by pulsed echo-Doppler, might reflect the portal vein pressure.…”
Section: Discussionmentioning
confidence: 99%